Enhancing the Effectiveness of Human Trafficking Crime Prevention Through Criminal Policy Reform, Digital Border Control, Social Protection Systems, and Whistleblowing Culture in Law Enforcement Institutions - Kris Tofel (Asosiasi Dosen Muda Indonesia, 2026)
Human trafficking remains one of the most complex transnational crimes affecting global human security, social justice, migration governance, labor systems, and international law enforcement mechanisms. Human trafficking networks continuously evolve through technological advancement, transnational migration flows, organized criminal syndicates, labor exploitation systems, online recruitment mechanisms, and weak institutional governance structures. Despite the existence of various international legal frameworks, including the Palermo Protocol and national anti-trafficking regulations, trafficking crimes continue to increase across developing and developed countries. This study aims to analyze strategies for enhancing the effectiveness of human trafficking crime prevention through criminal policy reform, digital border control systems, social protection systems, and whistleblowing culture in law enforcement institutions. The study employs a systematic literature review method by critically examining peer-reviewed international journal articles published between 2015 and 2026. The analysis integrates thematic analysis, comparative analysis, and narrative synthesis to identify major findings, governance patterns, institutional challenges, and policy implications regarding anti-human trafficking governance.